Early administration of gabapentinoids improves motor recovery after human spinal cord injury - Warner, Freda M.; Weidner, Norbert; Schuld, Christian (Cell reports, 2017)
Summary - The anticonvulsant pregabalin promotes neural regeneration in a mouse model of spinal cord injury (SCI). We have also previously observed that anticonvulsants improve motor outcomes following human SCI. The present study examined the optimal timing and type of anticonvulsants administered in a large, prospective, multi-center, cohort study in acute SCI. Mixed-effects regression techniques were used to model total motor scores at 1, 3, 6, and 12 months post injury. We found that early (not late) administration of anticonvulsants significantly improved motor recovery (6.25 points over 1 year). The beneficial effect of anticonvulsants remained significant after adjustment for differences in 1-month motor scores and injury characteristics. A review of a subset of patients revealed that gabapentinoids were the most frequently administrated anticonvulsant. Together with preclinical findings, intervention with anticonvulsants represents a potential pharmacological strategy to improve motor function after SCI.
Gesehen am 28.11.2018